If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7p+8=8p+p-8
We move all terms to the left:
7p+8-(8p+p-8)=0
We add all the numbers together, and all the variables
7p-(9p-8)+8=0
We get rid of parentheses
7p-9p+8+8=0
We add all the numbers together, and all the variables
-2p+16=0
We move all terms containing p to the left, all other terms to the right
-2p=-16
p=-16/-2
p=+8
| q-1=2q-10 | | 9x-7=9(x-1)+17 | | 9-5c=-7c-9 | | (2x-5)^(2)-(x-6)^(2)=80 | | h=2h-10 | | -z+4=z-8 | | 3+9b=8b | | -7(x-4)=2x+23 | | 4(p+3)-2=18 | | 2(3c+5)=82 | | -3k+10=7k | | `5x-2=23` | | -d=-2d-10 | | 9(4+c)=99 | | (H+2)x25=5 | | -12=2z | | 11y-2=3y+14 | | 15g=30/g= | | 52x-48=28x | | 6-3a=-10 | | -11=r+3 | | 180=6x+15x+33 | | 71=9x-47 | | 4(1-3x)=2(-4x+7) | | 4z+12+-14=26 | | 2u–6=5u-78 | | 5u–78=2u–6 | | 3v+81=15v+9 | | 4z+12+-14=26z=2 | | 2x-5=44=5x | | 3w+3w+3w+24=78 | | f+6=-11 |